Ablation Characteristics of Arterial Vessel Walls Irradiated with the Pulsed Dye Laser - An Analysis of Variance - Arndt, Volker R; Duda, Stephan H; Wehrmann, Manfred; Huppert, Peter E; Haase, Konstantin K; Claussen, Claus D (Thrombosis and Haemostasis, 1996)
Background and Objective: Since most clinical laser angioplasties require the use of over-the-wire delivery systems, we studied the effects of pulsed dye laser energy (504 nm, 1.4 μs) on arterial vessel walls in combination with a multifiber catheter system.Material and Methods: Postmortem arterial segments (n = 368) were exposed under blood or saline. Laser pulses (n = 100-800) were transmitted via 9F-multifiber-catheters, at energy densities of 3-16 J/cm2. Ablation characteristics revealed by histologic examination and morphometry were analyzed by multiple analysis of variance.Results: Ablation occurred more frequently in saline compared to blood. Below an energy density of 10 J/cm2 ablation occurred in saline only. Specimens irradiated under blood showed only thermal changes at 10 J/cm2. In saline, 92% of normal, 88% of fibro-fatty and 60% of calcified tissue showed ablation at 13 J/cm2. The average ablation threshold in saline was about 3-4 J/cm2 per pulse for normal tissue, 5 J/cm2 for fatty plaques, and 8-9 J/cm2 for calcified plaques. In blood, the average ablation thresholds did not differ significantly between the different stages of arteriosclerosis (12 J/cm2 for normal tissue, 11 J/cm2 for fatty plaque, and 10 J/cm2 for calcified tissue). Carbonization and vacuolization were seen regularly at energy levels ≥13.4 J/cm2.Conclusions: Selective ablation of arteriosclerotic tissue with the pulsed dye laser could not be found. Further investigation is needed before an effective ablation of arteriosclerotic arterial tissue can be expected.